Courseware on learning science for preschooler / Noor Hafizah Che Ali - Che Ali, Noor Hafizah (2006)
Courseware is a software used for teaching anc| learning purposes in a particular curriculum area, it can be used for any levels start from pre-school students, primary and secondary school students until university's students, but the way to present this courseware to every stage is definitely different from each other. Usually, it provides direct interactive learning in order to attract the audiences. The development of this project is to develop a courseware on learning Science for pre-school kids and teachers in order to provide them with interactive learning. This project only concern on preschool kids aged between five to six years old. The topics that covered in this development focused on basic learning of science such are human's body and introduction to animals and plants and their parts. Pedagogy is another important element that also included in this project. Therefore, many studies were conducted to apply pedagogy concepts in this courseware and considered certain suggestions from the preschool teachers to produce a quality courseware and achieve the objectives of this project. It is hoped that this courseware will give benefit to preschool kids by helping them to give proper understanding on the topics which were covered inside.